The Evolution and Population Diversity of Bison in Pleistocene and Holocene Eurasia: Sex Matters - Thierry Grange; Jean-Philip Brugal; Laurence Flori; Mathieu Gautier; Antigone Uzunidis; Eva-Maria Geigl (Diversity, 2018)
Knowledge about the origin and evolutionary history of the bison has been improved recently owing to several genomic and paleogenomic studies published in the last two years, which elucidated large parts of the evolution of bison populations during the Upper Pleistocene and Holocene in Eurasia. The produced data, however, were interpreted in contradicting manners. Here, we have gathered, reanalyzed and compared previously published or unpublished morphometric and genetic data that have not yet been integrated and that we synthesize in a unified framework. In particular, we re-estimate dates of divergence of mitogenome lineages based on an extended dataset comprising 81 complete ancient bison mitogenomes and we revisit putative gene flow between the Bos and Bison genera based on comparative analyses of ancient and modern bison genomes, thereby questioning published conclusions. Morphometric analyses taking into account sexual dimorphism invalidate a previous claim that Bison schoetensacki was present in France during the Late Pleistocene. Both morphometric and genome analyses reveal that Eurasian bison belonging to different Bison priscus and Bison bonasus lineages maintained parallel evolutionary paths with gene flow during a long period of incomplete speciation that ceased only upon the migration of B. priscus to the American continent establishing the American bison lineage. Our nuclear genome analysis of the evolutionary history of B. bonasus allows us to reject the previous hypothesis that it is a hybrid of B. priscus and Bos primigenius. Based on present-day behavioral studies of European and American bison, we propose that apparently conflicting lines of evidence can be reconciled by positing that female bison drove the specialization of bison populations to different ecological niches while male bison drove regular homogenizing genetic exchanges between populations.